Effectiveness of using compression garments in winter racing sports: a narrative review - Yang, C.; Xu, Y.; Yang, Y.; Xiao, S.; Fu, W. (Frontiers in Physiology, 2020)
Nowadays, compression garments (CGs) are widely used in winter racing sports, such as speed skating, short-track speed skating, alpine skiing, and cross-country skiing. However, the effect of wearing CGs on athletic performance in these specific sports is still not fully examined. Thus, the aim of this narrative review is to summarize the research and application of CGs in winter racing sports and to discuss how the CGs help athletes improve their performance in an integrative manner (i.e., physiology, aerodynamics, and biomechanics). A total of 18 experimental studies dedicated to CGs in winter racing sports were identified from the peer-review scientific literature. The main findings are as follows. (1) Currently, CG studies have mainly focused on drag reduction, metabolism, muscle function, strength performance, and fatigue recovery. (2) The results of most studies conducted in wind tunnels showed that, for cylindrical structures similar to the human body, clothing with rough surfaces can reduce air drag. Notably, the effect of CGs on drag reduction in real competition has not been fully explored in the literature. (3) Compression can reduce muscle vibrations at high impact and help athletes control the center of pressure movement, a function that is important for alpine skiing. Future studies are needed to improve current understanding of the effects of compression clothing microstructure on drag reduction and their stretching in different parts of the body. Furthermore, the design of experimental protocol must be consistent with those during the competition, thus providing a full discussion on energy metabolism, fatigue, and recovery affected by CGs.